Comparison of Doses in Organs at Risk of Conventional and Three-Dimensional Treatment Planning in Hybrid Brachytherapy - Chen, Suk Chiang; Mohd Ramli, Fathin Atika; Abdullah, Reduan; Mohd Zahri, Abdul Aziz (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: This retrospective study aims to evaluate the doses of organs at risk (OARs) calculated by conventional two-dimensional (2-D) and three-dimensional (3-D) treatment planning techniques in hybrid high dose rate (HDR) brachytherapy for cervical cancer. MATERIALS AND METHODS: Data of five patients treated with combination of intracavitary and interstitial brachytherapy were used. For each implant, computed tomography (CT) images were obtained, and the clinical target volume and OARs were contoured on CT images. In 3-D planning, the volumes of OARs were derived from dose-volume histogram (DVH) on a dose volume of 2 cc for bladder, rectum, and sigmoid. The OARs defined in replanning for 2-D treatment were the ICRU-38 bladder (bICRU) and rectum (rICRU) points. Paired T-tests were used to analyse the radiation doses of bladder and rectum obtained from both techniques. RESULTS: The mean point doses evaluated via bICRU) and rICRU were 89.34 GyEQD2 and 75.92 GyEQD2, respectively. Meanwhile, the mean volumetric doses of D2cc for bladder and rectum were 80.50 GyEQD2 and 69.08 GyEQD2, respectively. There is a significant difference in mean doses of ICRU point and D2cc volume for bladder (p<0.05). However, there is no significant difference in mean doses of ICRU point and D2cc for rectum (p>0.05). Overall, ICRU point doses overestimated volumetric D2cc doses with a mean dose ratio of 1.110 for bladder and 1.099 for rectum respectively. CONCLUSION: The bICRU in 2-D planning could not represent the bladder 2 cc used in 3-D planning, thus resulting in different total dose; whereas rICRU of 2-D planning was discovered to be similar with rectum 2 cc of 3-D planning and deemed reliable in total dose estimation